PENINGKATAN KOMPETENSI MERUMUSKAN INDIKATOR DAN TUJUAN PEMBELAJARAN MELALUI SUPERVISI AKADEMIK BAGI GURU KELAS SD NEGERI 1 BALEPANJANG TAHUN PELAJARAN 2018/2019 - Suparni Suparni (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2020)
AbstractThis study aims to improve competency in formulating indicators and learning objectives for class I to VI SDN 1 Balepanjang District Baturetno District Wonogiri District Semester I Academic Year 2018/2019 through academic supervision This research uses the School Action Research method which is carried out in 2 cycles. The setting of this research is SDN 1 Balepanjang. The research subjects were 6 class teachers consisting of class I to VI teachers at SD Negeri 1 Balepanjang. Data collection techniques are non-test, in the form of documents, observations / supervision, and field notes to determine teacher competence in formulating indicators and learning objectives. The results of this research can be concluded that there was an increase in competency in formulating learning objectives after being given academic supervision for grade I to VI teachers of SDN 1 Balepanjang, Baturetno District, Wonogiri Regency Semester I, 2018/2019 academic year, from 1 person or 16.7% of the teachers have the competence to formulate learning objectives in both categories in the pre cycle, in the first cycle to 5 people or 83.3% and in the second cycle to 6 teachers or 100%. With a pre-cycle average of 68, it becomes 81 in cycle I and in cycle II it becomes 88Keywords: Teacher Competence, Indicators, Learning Objectives Academic Supervision